Development of Quran-Based Nahwu Tatbĩqi Teaching Materials to Improve Understanding of Verbal and Nominal Sentence Meanings - Hula, Ibnu Rawandhy N.; Mahmud, Moh andika Satrio (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Understanding Arabic syntax, especially verbal (jumlah fi‘liyyah) and nominal sentences (jumlah ismiyyah), is essential for comprehending Qur’anic texts. However, grammar learning in schools often remains theoretical and lacks contextual application. This study aims to develop Quran-based Nahwu Tatbiqi teaching materials to enhance students’ practical understanding of these sentence structures. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Participants included Madrasah Aliyah students and Arabic teachers, with data collected through questionnaires, tests, expert validation sheets, and observations. Expert validation in media, content, and language confirmed the feasibility of the product. The materials were then tested through field implementation with a pretest–posttest design. Data analysis employed SPSS 27 using descriptive and inferential statistics. Findings indicate that the developed materials are valid and effective, demonstrated by a significant increase in students’ average scores from 62.15 (pretest) to 82.47 (posttest). This improvement shows that integrating theoretical grammar with Qur’anic-based contextual practice bridges the gap between abstract knowledge and applied understanding. The results confirm that the developed teaching materials enhance grammatical comprehension and provide meaningful contributions to Arabic learning in educational institutions. Moreover, this study suggests further exploration of similar context-based materials for other aspects of Arabic language learning to enrich pedagogical practices.